Feasibility of using dry extracts of tea in the food industry - Rubanka, Kateryna; Terletska, Vita; Bobel (Zinchenko), Inna; Falendysh, Natalia (My University, 2015)
The article is devoted for the use of extracts as a source o f biologically active substances in food products balanced on vitamins and minerals. Quantitative changes o f the content o f water-soluble vitamins and minerals o f green and black tea in the production o f dry tea extracts have been ascertained.
Keywords: tea; extracts; vitamins; minerals; чай; екстракти; вітаміни; мінеральні речовини; кафедра технології хлібопекарських і кондитерських виробів; экстракты; витамины; минеральные вещества